Public finance - Hicks, Ursula K. (London : Nisbet, 1947)
The book examines the issues of public finance in Great Britain both in private and public sector.
Includes index
Includes bibliographic references
usc 25/01/2019
Loans
Keywords: Finance; Finance, Public; Taxation; Great Britain